2014
DOI: 10.1097/inf.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Surveillance in the United States, 2007–2012

Abstract: Background:Annual respiratory syncytial virus (RSV) outbreaks throughout the US exhibit variable patterns in onset, peak month of activity and duration of season. RSVAlert®, a US surveillance system, collects and characterizes RSV test data at national, regional, state and local levels.Methods:RSV test data from 296 to 666 laboratories from 50 states, the District of Columbia and Puerto Rico (as of 2010) were collected during the 2007–2008 to 2011–2012 RSV seasons. Data were collected in early August/September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 14 publications
4
27
0
Order By: Relevance
“…In Northern Europe, IAV epidemics are concentrated in the winter months, and the peak is usually in February [14]. RSV epidemics occur simultaneously with IAV, and the peak is in February, but with a wider time span [14,15]. Our results were in concordance with these reports: the IAV peak was commonly detected between weeks 7 and 9, whereas the annual RSV peak had a wider range (from week 7 in 2012 to week 14 in 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Northern Europe, IAV epidemics are concentrated in the winter months, and the peak is usually in February [14]. RSV epidemics occur simultaneously with IAV, and the peak is in February, but with a wider time span [14,15]. Our results were in concordance with these reports: the IAV peak was commonly detected between weeks 7 and 9, whereas the annual RSV peak had a wider range (from week 7 in 2012 to week 14 in 2014).…”
Section: Discussionsupporting
confidence: 91%
“…For example, IAV and RSV circulation shows a wave-like pattern, whereas adenovirus is present throughout the year. It is also commonly known that RSV causes larger epidemics biannually [15,20], which could also be seen in our material: RSV was detected more frequently in samples in 2012 and 2014 compared to 2013 ( Table 2 and Fig. 3).…”
Section: Discussionsupporting
confidence: 85%
“…In a study conducted in Egypt by Shafik et al [5] aiming to identify the relative prevalence of various respiratory viruses that contribute to LRTIs in young children under five years of age, RSV was determined to be the predominant viral agent among children with LRTI using RT-PCR; also, RSV could only be detected from November through midFebruary. Another study by McGuiness et al [15] estimating the RSV season in the United States by the Centers for Disease Control and Prevention found that the RSV season onset occurred in October/November of each year with an offset occurring in March/April of the following year. Also, Leung et al [16] found that RSV-associated PICU admissions in Hong Kong appeared to follow the overall pattern of RSV outbreaks, which usually begin in November or December, peak in January or February, and end by the end of March or sometime in April.…”
Section: Discussionmentioning
confidence: 99%
“…RSV tests were conducted for all study weeks from 2001 to 2013. For this study, the RSV outbreak periods were defined as consecutive MMWR weeks with at least 10% positive diagnostic tests, as has been done in past studies [2,3]. The same criterion, that is, consecutive weeks with at least 10% positive tests, was used to define the flu outbreak periods in order to maintain a consistent approach for the 2 respiratory viruses.…”
Section: Surveillance Datamentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) is a well-recognized, common cause of severe lower respiratory tract illness and hospitalization in children [1]. More recently, the contribution of adult RSV infections to the utilization of advanced healthcare resources, morbidity, and mortality has become increasingly clear [2][3][4][5][6][7]. Introduction of diagnostic real-time reverse-transcription polymerase chain reaction assays for viral testing has improved identification of RSV infections and increased awareness of the prominent role this respiratory virus has in relatively severe illness in adults [5,6,8,9].…”
mentioning
confidence: 99%